Hubungan Peran Keluarga dengan Kepatuhan Minum Obat Klien TB Paru di Puskesmas Tlogosari Kulon - Nafiatun Khasanah; Moch. Aspihan; Iskim Luthfa (Lembaga Pengembangan Kinerja Dosen, 2025)
Pulmonary tuberculosis (TB) is a public health problem of concern because of its contagious nature. Success in treating pulmonary TB, which is very important to prevent drug resistance, is largely determined by patient compliance in taking medication regularly. However, the most important factor in the diagnosis of this disorder is the extent to which recommendations are followed. Therefore, the task of the family exercise monitor (PMO) is very important in helping the patient accept the forced teaching. The aim of this research is to analyze family members on the health status of pulmonary tuberculosis patients who come to take medication at the Tlogosari Kulon Health Center. The design in this research analysis is cross-sectional correlation, specifically to test the relationship between two variables at the same time. This sample consisted of 71 cases of pulmonary tuberculosis registered at Balai Tlogosari Kulon. At this institution, a cross-sectional correlation analysis design is used to analyze the relationship between two variables over a period of time. The sample in this study was 71 TB patients registered at the Tlogosari Kulon Health Center. Purposive sampling is a sample collection technique used, where respondents are carefully selected based on predetermined criteria to ensure they meet the research objectives. The tool used to accumulate data is a questionnaire, which is designed to collect information about the variables studied. The data obtained from the questionnaire was then analyzed using the Chi-square test to analyze whether there was a significant relationship between these variables. The results of the study explained that the majority of respondents, namely 40 people (56.3%), rated the family's role as Medication Monitoring Supervisor (PMO) in the good category, while 28 respondents (39.4%) showed good compliance in taking medication. The Chi-square test results show that the significance value is p = 0.003, (<0.05). This shows that the null hypothesis (H0) is rejected. This research can be concluded that there is a relationship between the role of the family and compliance with taking medication for pulmonary TB clients at the Tlogosari Kulon Community Health Center.